Therapeutic Prospects of Abemaciclib for Patients with Endometrial Cancer - Ahmad Awada; Sarfraz Ahmad (Current Oncology)
Endometrial cancer (EC) is a common gynecologic malignancy with a rising incidence due to obesity, comorbid conditions, and related lifestyle factors. The standard of care for primary disease consists of surgical resection with/without chemotherapy ± radiotherapy for select patients. Recurrence is common in patients with advanced-stage disease and/or high-risk features, who primarily are treated with systemic therapy. The identification of novel targets in malignant EC has led to the development of wide-range inhibitors. Abemaciclib is an orally active unique cyclin-dependent kinase (CDK) inhibitor, selective for the CDK4 and CDK6 cell cycle pathways. This agent has potential anti-neoplastic activity and is indicated in combination with various therapies such as endocrine therapy, aromatase inhibitors, and hormone therapies, primarily in breast cancer (BC). Herein, we sought to summarize the biochemical/pharmacological properties of abemaciclib and its therapeutic potential in EC. While the therapeutic role(s) of abemaciclib was fairly established in a subset of patients with advanced/metastatic BC through the pivotal MONARCH trials, its attributes and clinical utility in EC are limited. Thus, based on some promising pre-clinical/translational insights and a recent phase II study, we highlight abemaciclib’s properties and potential clinical usefulness in patients with EC, particularly in recurrent estrogen-receptor-positive cases.